Red blood cells in proliferative kidney disease—rainbow trout (Oncorhynchus mykiss) infected by Tetracapsuloides bryosalmonae harbor IgM+ red blood cells - Chan, Justin T. H.; Picard-Sánchez, Amparo; Majstorović, Jovana; Rebl, Alexander; Koczan, Dirk; Dyčka, Filip; Holzer, Astrid S.; Korytář, Tomáš (Frontiers in Immunology, 2023)
The myxozoan parasite Tetracapsuloides bryosalmonae is the causative agent of proliferative kidney disease (PKD)—a disease of salmonid fishes, notably of the commercially farmed rainbow trout Oncorhynchus mykiss. Both wild and farmed salmonids are threatened by this virulent/deadly disease, a chronic immunopathology characterized by massive lymphocyte proliferation and hyperplasia, which manifests as swollen kidneys in susceptible hosts. Studying the immune response towards the parasite helps us understand the causes and consequences of PKD. While examining the B cell population during a seasonal outbreak of PKD, we unexpectedly detected the B cell marker immunoglobulin M (IgM) on red blood cells (RBCs) of infected farmed rainbow trout. Here, we studied the nature of this IgM and this IgM+ cell population. We verified the presence of surface IgM via parallel approaches: flow cytometry, microscopy, and mass spectrometry. The levels of surface IgM (allowing complete resolution of IgM- RBCs from IgM+ RBCs) and frequency of IgM+ RBCs (with up to 99% of RBCs being positive) have not been described before in healthy fishes nor those suffering from disease. To assess the influence of the disease on these cells, we profiled the transcriptomes of teleost RBCs in health and disease. Compared to RBCs originating from healthy fish, PKD fundamentally altered RBCs in their metabolism, adhesion, and innate immune response to inflammation. In summary, RBCs play a larger role in host immunity than previously appreciated. Specifically, our findings indicate that the nucleated RBCs of rainbow trout interact with host IgM and contribute to the immune response in PKD.